GE_GERICHTE A/2968/2018 vom 13. Dezember 2018 - GE Cour de justice (2018)
Séquestre; assiette du séquestre; estimation des biens séquestrés; risque de change | LP.97.al1; LP.97.al2; LP.275; LP.276.al1; LP.88.al4